Analisis Pengaruh Pengalaman Berorganisasi di PMII Terhadap Kinerja Usaha Alumni: Studi Kasus Komisariat Bela Negara UPN "Veteran" Jawa Timur - Hutama Muhammad Anhar (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study examines the influence of organizational experience within PMII on the business performance of its alumni through an empirical qualitative case study approach. The research focuses on alumni of the Bela Negara Commissariat at UPN “Veteran” East Java who have actively managed businesses for at least one year. Data were collected through in-depth interviews, limited participatory observation, and documentation, and analyzed using an interactive model involving data reduction, display, and verification. The findings reveal that organizational experience contributes significantly to the development of leadership, communication, problem-solving, and networking competencies, which are subsequently transformed into strategic business practices. The study also identifies relational patterns indicating that experiential learning processes shape adaptive capacity, innovation orientation, and business sustainability. The results reinforce the human capital perspective, emphasizing that intangible competencies derived from organizational engagement play a crucial role in entrepreneurial success. This research contributes to the discourse on experiential learning and entrepreneurship by providing contextual evidence of how student organizational involvement fosters practical capabilities that enhance business performance in real-world settings.